Age-specific kinetics of neutralizing antibodies and infection enhancement among ≤1 year-old Indian infants - Chelluboina, Shweta; Mishra, Akhilesh Chandra; Arankalle, Vidya Avinash; Shrivastava, Shubham (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundInfants born to dengue-immune mothers acquire maternal antibodies to dengue. Maternal antibodies decline over time, making infants susceptible to primary dengue infections. Another important concern is the role of maternal antibodies in causing antibody-dependent enhancement (ADE) during primary infections. In this study, we aimed to investigate the kinetics of dengue virus (DENV)-neutralizing antibodies and infection-enhancing activity in Indian infants.MethodsHealthy infants at birth (cord blood), and at 3, 6, 9, and 12 months of age (n=32/group) were included in this cross-sectional study. Serum samples were tested for neutralizing antibodies using the foci-reduction neutralization test and enhancing antibodies using the ADE assay against DENV1-4 serotypes.ResultsNeutralizing antibody positivity declined with the increasing age of the infants. Undetectable levels of neutralizing antibodies to DENV1-4 serotypes were reported in 84% of infants by 9 months. Significantly lower neutralizing antibody titers were also reported in 9-month-old infants compared to that in 6-month-old infants and infants at birth. Comparable levels of enhancement of DENV1-4 infection at a particular dilution to at least one serotype were noted in infants at 3 and 6 months of age. Fold enhancement of DENV1-4 infection was found to be highest in 6-month-old infants at a dilution of 1:20. In summary, our data suggests that DENV infection–enhancing activity aligns with the decline of neutralizing antibodies.ConclusionOur study indicates that maternally acquired neutralizing antibodies could be protective until 6 months of age and capable of facilitating ADE on exposure to dengue infections in later months of life.